2016
DOI: 10.4251/wjgo.v8.i9.642
|View full text |Cite
|
Sign up to set email alerts
|

Role of targeted therapy in metastatic colorectal cancer

Abstract: Colorectal cancer (CRC) is a significant cause of cancer-related morbidity and mortality all over the world. Improvements of cytotoxic and biologic agents have prolonged the survival in metastatic CRC (mCRC), with a median overall survival of approximately 2 years and more in the past two decades. The biologic agents that have proven clinical benefits in mCRC mainly target vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR). In particular, bevacizumab targeting VEGF and cetuxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 92 publications
(100 reference statements)
0
73
1
2
Order By: Relevance
“…However, the majority of patients with metastatic CRC (mCRC) experience a poor survival rate (3,4). A growing body of research has demonstrated the positive effect of molecularly targeted treatment on the survival rate of patients with mCRC, especially with the use of monoclonal antibodies against epidermal growth factor receptor (EGFR) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients with metastatic CRC (mCRC) experience a poor survival rate (3,4). A growing body of research has demonstrated the positive effect of molecularly targeted treatment on the survival rate of patients with mCRC, especially with the use of monoclonal antibodies against epidermal growth factor receptor (EGFR) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions contributed to a complete response of the liver metastases and an overall survival time of 29 months. The literature suggests that the median overall survival time for patients with mCRC, following combinational or sequential use of active drugs and molecules, is ~24 months (26).…”
Section: Discussionmentioning
confidence: 99%
“…At the time of data collection for mCRC diagnosis year 2011, NCCN guidelines recommended testing for the KRAS oncogene only among mCRC patients [14]. However, the evolution of recent research found that mCRC patients with RAS mutations on the KRAS as well as the NRAS oncogene do not respond to anti-EGFR treatment either [15-17]. NCCN currently recommends genotyping tumor tissue for both KRAS and NRAS mutations for mCRC giving a result of either normal (wild-type) and able to receive anti-EGFR treatment; or a mutated status and should not be treated with anti-EGFR treatment [18].…”
Section: Introductionmentioning
confidence: 99%